Comprehensive review of Calophyllum inophyllum as a feasible alternate energy for CI engine applications. (November 2019) - Vigneshwar, V.; Krishnan, S. Yogesh; Kishna, R. Susanth; Srinath, R.; Ashok, B.; Nanthagopal, K.
Abstract: Tree seed oils seem to be a transportation fuel for compression ignition engine at the regular usage around the globe. In India, the seven out of eight customers prefer to use diesel vehicles for their regular usage which has depicted a highly crooked situation. In this present report, a comprehensive review of Calophyllum inophyllum biodiesel as alternative energy source for compression ignition engine applications through various categories like properties assessment, utilization in diesel engine etc. This review report summarizes the various novel production technologies for Calophyllum inophyllum biodiesel that have been used in recent times along with their production yield comparative analysis. Many optimized production methodologies of Calophyllum inophyllum biodiesel have been comparatively evaluated with other feedstock based biodiesels. It has been noticed that the raw oil per Calophyllum inophyllum tree would be around 11.7 kg and Calophyllum inophyllum biodiesel yield through supercritical intensification method is closed to 99% which is significantly higher than other biodiesel feedstock. Further, the impacts of Calophyllum inophyllum biodiesel properties on compression ignition engine behaviours were eventually outlined. Inaddtion, the recent research outputs on the effect of various higher alcohols, antioxidants and nanoparticles with Calophyllum inophyllum biodiesel fuel at various concentrations are discussed in a comprehensive manner. The overall influence of changing compression ignition engine operating parameters such as injection timing, injection pressure and compression ratio variations during Calophyllum inophyllum biodiesel fuel operations are critically outlined. Inaddtion, the various properties of Calophyllum inophyllum biodiesel are compared with other feedstock biodiesels and fewer experimental work outputs are highlighted. In the end, the life cycle cost analysis of Calophyllum inophyllum biodiesel has also been presented. Finally, some specific conclusions about Calophyllum inophyllum biodiesel are summarized and few critical problems on the commercial utilization of Calophyllum inophyllum biodiesel are also pointed out. Highlights: Critical review of various production methodologies of CIME. Calophyllum inophyllum fuelled in Compression Ignition engine is reviewed. Effects of additives such as alcohols, ether, nanoparticles and ethers are examined. Effect of various engine operating parameters for CIME operation is critically analysed. Highlighted the future scope of research for CIME as fuel alternative fuel.